1988
DOI: 10.1016/0014-5793(88)80778-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of [hydroxyproline3]‐lysyl‐bradykinin released from human kininogens by human urinary kallikrein

Abstract: The types of kinins released from purified native, single chain human high and low molecular mass kininogens (HMMKs and LMMKs, respectively) by purified human urinary kallikrein were separated by reverse-phase HPLC and quantitated by the rat uterus bioassay.[Hy@]-lysyl-bradykinin, a recently discovered kinin, represented up to 58% of the biological activity released from 4 individual HMMK preparations purified from 4 different healthy volunteers. In contrast, the majority of the biological activity released fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 19 publications
(3 reference statements)
0
6
0
Order By: Relevance
“…bradykinin (BK) and hydroxyprolyl 3-bradykinin (Arg-Pro-Hyp-Gly-Phe-Ser-Pro-Phe-Arg), (Hyp 3-BK), in human tumor ascites and concluded that they are generated from high molecular weight kininogen [7,8]. We and other workers have also identified Hyp3-BK from normal human plasma or urine [9][10][11][12]. Because of the large capacity of generation of kinins and the potent activity of these peptides, they may be important in various pathological conditions.…”
Section: Introductionmentioning
confidence: 92%
“…bradykinin (BK) and hydroxyprolyl 3-bradykinin (Arg-Pro-Hyp-Gly-Phe-Ser-Pro-Phe-Arg), (Hyp 3-BK), in human tumor ascites and concluded that they are generated from high molecular weight kininogen [7,8]. We and other workers have also identified Hyp3-BK from normal human plasma or urine [9][10][11][12]. Because of the large capacity of generation of kinins and the potent activity of these peptides, they may be important in various pathological conditions.…”
Section: Introductionmentioning
confidence: 92%
“…Astonishingly enough, hydroxyla tion was found to vary widely between human H-and Lkininogen, respectively. Maier et al reported that Hyp3-Lysbradykinin represented 47% (range 30 to 59% , n = 4) of the total kinin peptides released from purified H-kininogen, whereas it was only 6% (from pool plasma) in the case of L-kininogen (19). The reason for this unexpected "differential" hydroxylation is unknown at the moment.…”
Section: Hydroxylation Of Kininogens and Kininsmentioning
confidence: 99%
“…Now these seem ingly contradictory observations have been reconciled. Four research groups including Scicli's team independently demon strate that Ala was incorrectly assigned to position 3 (18)(19)(20)(21)(22). Instead, 4-hydroxy-proline (Hyp) was identified in this position thus pointing to a post-translational modification of Pro in position 3.…”
Section: Hydroxylation Of Kininogens and Kininsmentioning
confidence: 99%
See 2 more Smart Citations